Evaluation of work safety through the use of FMEA, based on NR-18: case study in a vertical building in Imperatriz - MA - Jorge, Gustavo Pires do Nascimento (Brazilian Journal of Production Engineering, 2023)
The Engineering branch has had a major growth highlight in recent years, specifically the area of ​​civil construction. However, with this growth, the number of accidents has increased, due to the lack of risk management and control. Safety management is essential in any undertaking, and based on this premise, this article aims to evaluate, based on the Regulatory Norms (NR 6, 18 and 35), the risks in a vertical work in the city of Imperatriz-MA, and through from the application of the FMEA tool, to present alternatives to minimize or eliminate the causes of these risks, constituting them mainly due to the lack of training and EPC. Therefore, it is noted that the FMEA Tool has great potential and effectiveness in the field of work safety.